Fecal Microbiota Transplantation for Recurrent Clostridium difficile Infection and Other Conditions in Children: A Joint Position Paper From the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition and the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition. Issue 1 (January 2019) - Davidovics, Zev H.; Michail, Sonia; Nicholson, Maribeth R.; Kociolek, Larry K.; Pai, Nikhil; Hansen, Richard; Schwerd, Tobias; Maspons, Aldo; Shamir, Raanan; Szajewska, Hania; Thapar, Nikhil; de Meij, Tim; et al.
Abstract : ABSTRACT: Fecal microbiota transplantation (FMT) is becoming part of the treatment algorithms against recurrent Clostridium difficile infection (rCDI) both in adult and pediatric gastroenterology practice. With our increasing recognition of the critical role the microbiome plays in human health and disease, FMT is also being considered as a potential therapy for other disorders, including inflammatory bowel disease (Crohn disease, ulcerative colitis), graft versus host disease, neuropsychiatric diseases, and metabolic syndrome. Controlled trials with FMT for rCDI have not been performed in children, and numerous clinical and regulatory considerations have to be considered when using this untraditional therapy. This report is intended to provide guidance for FMT in the treatment of rCDI in pediatric patients. Abstract : Supplemental Digital Content is available in the text